The Position of Women in Islamic History - Siregar, Ahmad Rajab; Badrun, Badrun (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
During the pre-Islamic era, women were considered like goods sold in the market. After Islam came, the position of women began to be equalized with men. Islam teaches that men and women have the same position. Even so, it turns out that in practice this is not the case. In Islamic history until today, even in Islamic countries, the position of men is still higher than women. This research aims to analyze the position of women from the time of the prophet to the era of the Ottoman Turkish dynasty. This research uses historical research methods to examine the topic under study. The result of this research is that gender equality taught by the prophet has not been fully implemented, because there are challenges from the culture and thinking of the community. Women during the time of the prophet until Khulafa al-Rashidun were only limited to the intellectual field (religion). They began to be involved in social and political fields from the Umayyad Dynasty to Ottoman Turkey. The small number of women who appear in history proves that gender equality has not been achieved.